Smile restoration through use of enamel mricroabrasion associated with tooth bleaching - Sundfeld, Renato Herman; Rahal, Vanessa; Alexandre, Rodrigo Sversut de; Briso, André Luiz Fraga [UNESP]; Sundfeld Neto, Daniel (My University, 2011)
Enamel microabrasion can eliminate enamel irregularities and discoloration defects, improving the appearance of teeth. This article presents the latest treatment protocol of enamel microabrasion to remove stains on the enamel surface. It has been verified that teeth submitted to microabrasion acquire a yellowish color because of the thinness of the remaining enamel, revealing the color of dentinal tissue to a greater degree. In these clinical conditions, correction of the color pattern of these teeth can be obtained with a considerable margin of clinical success using products containing carbamide peroxide in custom trays. Thus, patients can benefit from combined enamel microabrasion/tooth bleaching therapy, which yields attractive cosmetic results. Esthetics plays an important role in contemporary dentistry, especially because the media emphasizes beauty and health. Currently, in many countries, a smile is considered beautiful if it imitates a natural appearance, with clear, well-aligned teeth and defined anatomical shapes.1-3 Enamel microabrasion is one technique that can be used to correct discolored enamel. This technique has been elucidated and strongly advocated by Croll and Cavanaugh since 1986,4 and by other investigators1,2,5-13 who suggested mechanical removal of enamel stains using acidic substances in conjunction with abrasive agents. Enamel microabrasion is indicated to remove intrinsic stains of any color and of hard texture, and is contraindicated for extrinsic stains, dentinal stains, for patients with deficient labial seals, and in cases where there is no possibility to place a rubber dam adequately during the microabrasion procedure.1,2 It should be emphasized that enamel microabrasion causes a microreduction on the enamel surface,3,6,10 and, in some cases, teeth submitted to microabrasion may appear a darker or yellowish color because the thin remaining enamel surface can reveal some of the dentinal tissue color. In these situations, according to Haywood and Heymann in 1989,14 correction of the color pattern of teeth can be obtained through the use of whitening products containing carbamide peroxide in custom trays. A considerable margin of clinical success has been shown when diligence to at-home protocols is achieved by the patient and supervised by the professional.3 Considering these possibilities, this article presents the microabrasion technique for removal of stains on dental enamel, followed by tooth bleaching with carbamide peroxide and composite resin restoration, if required.
Keywords: Enamel microabrasion; Dental bleaching; Case reports